Micropillar compression study of Fe-irradiated 304L steel. (November 2019) - Paccou, Elie; Tanguy, Benoît; Legros, Marc
Abstract: To assess the irradiation induced hardening and the modification of deformation modes at the grain scale on 304L steels used in irradiated structural components in nuclear reactors, in situ microcompression tests were conducted on irradiated and non-irradiated FIB-made pillars. To surrogate neutron irradiation, steel plates went through 10 MeV Fe-ions irradiations up to 8 dpa at 450 °C. Size effect was detected on unirradiated but not on irradiated pillars, revealing a strong impact of the microstructure on the mechanical behavior. TEM investigations may also have helped understanding the smoother plastic deformation in irradiated pillars. Graphical abstract: Unlabelled Image